Principles of chemistry a molecular approach - Tro, Nivaldo J. (Pearson Education Limited, 2016)
For two-semester courses in General Chemistry. A relevant, problem-solving approach to chemistry The Third Edition of Principles of Chemistry: A Molecular Approach presents core concepts without sacrificing rigor, enabling students to make connections between chemistry and their lives or intended careers. Drawing upon his classroom experience as an award-winning educator, Professor Tro extends chemistry to the student's world by capturing student attention with examples of everyday processes and a captivating writing style. Throughout this student-friendly text, chemistry is presented